The Use of the Langgar Bubrah Historical Site as a Social Studies Learning Resource at the Junior High School Level - Fu'adah, Laily; Tawandorloh, Ku-Ares (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2022)
Not only books, learning history can also be done by coming directly to historical sites, such as the bubrah mosque which can be used as a social study learning resource on the life of Indonesian society. The purpose of this study was to determine the utilization and relevance of the historical site of langgar bubrah as a social study learning resource. This study uses a qualitative method with a descriptive approach. Data collection by interview, observation and documentation methods. The results of this study indicate that Langgar Bubrah is a historical relic of the Hindu-Buddhist and Islamic period with some evidence of the types of buildings and religious elements contained therein. There is a relevance of social studies learning with the breaking bubrah site, so that the site can be used as a social study learning resource for class VII KD 3.4. It is hoped that this research will be able to provide a more comprehensive understanding of the material and students will get messages of value from historical events related to the Bubrah Langar site.